Model for financing the agro-industrial complex of the region - M. B. Trachenko; V. V. Kudashov (Вестник университета)
The article deals with the problems of financing the agro-industrial complex of the region. A critical assessment of the current model of state support for agricultural organisations is given. It was revealed that when deciding on the allocation of subsidies, the region is guided exclusively by production indicators and does not assess the impact of subsidies on the financial condition of agricultural producers in the future. It is proposed that the assessment of the effectiveness of the provision of subsidies be supplemented in regional state programs for the development of agriculture by comparing the volumes of loans issued and the added value created for a certain period. A universal model of financing the agro-industrial complex of the Russian region has been developed, which makes it possible to choose the most effective option for the distribution of budgetary financing of agricultural organizations in a particular region.